Long Live the Vacancy - Christian Haefke; Michael Reiter (Institute of Labor Economics (IZA), 2020)
We reassess the role of vacancies in a Diamond-Mortensen-Pissarides style search and matching model. In the absence of free entry long lived vacancies and endogenous separations give rise to a vacancy depletion channel which we identify via joint unemployment and vacancy dynamics. We show conditions for constrained efficiency and discuss important implications of vacancy longevity for modeling and calibration, in particular regarding match cyclicality and wages. When calibrated to the postwar US economy, the model explains not only standard deviations and autocorrelations of labor market variables, but also their dynamic correlations with only one shock.
Keywords: E24; E32; J63; J64; 330; Beveridge curve; business cycles; job destruction; random matching; separations; unemployment volatility; wage determination